Accounting function outsourcing among Iranian SMEs and its impact on firm performance / Yahya Kamyabi - Yahya, Kamyabi (2012)
The primary objective of this study is to examine the factors affecting accounting function outsourcing and the impact of such outsourcing on SME performance from perspective of Transaction Cost Economics (TCE) and Resource- Based Views (RBV) in the Iranian context. Seven important TCE and RBV variables (factors) influencing on outsourcing intensity are identified, namely: asset specificity, environmental uncertainty, behavioural uncertainty, frequency, trust, technical competence and degree of competition. More importantly, this study examines the mediating role of accounting function outsourcing. 1750 questionnaires were mailed to Iranian manufacturing SMEs and only 658 usable questionnaires were utilised, representing an effectual response rate of 37.6 percent. Data analysis using structural equation model (SEM) revealed that with the exception of environmental uncertainty and behavioural uncertainty, the five remaining factors (i.e., asset specificity, frequency, trust, technical competence and degree of competition) are significantly associated with accounting function outsourcing intensity. Interestingly, the results show that the accounting function outsourcing intensity is significantly and positively associated with SME performance. Furthermore, whilst the fully mediated model shows outsourcing to be a non-mediator in the links between environmental uncertainty and behavioural uncertainty and firm performance, it is a strong mediator in the case of asset specificity, frequency, trust, technical competence and degree of competition and firm performance links. This study contributes to the body of knowledge of accounting particularly in highlighting the important role of professional accountants in enhancing SME development. As for SME owner-managers, this study confirms the significant factors that influence the decision to outsource the accounting function geared towards achieving higher SME performance. In short, SME owner-managers and accounting practitioners are advanced one step further by the research findings.